Navigating electives: Perspectives from phase III MBBS students and faculty in program evaluation - Sujatha Karjigi; Shyamala KK; Divya Gupta; Karthik R (Asian Journal of Medical Sciences)
Background: An elective is a learning experience created in the competency-based medical education curriculum to provide an opportunity for the learner to explore, discover, and experience areas or streams of interest in the profession. To implement a program successfully, we need to continuously evaluate the program and make necessary revisions based on feedback, outcomes, and challenges faced.